Evaluation of the influence of smear layer removal on the sealing ability of two different obturation techniques - Kerem Engin Akpınar; Dilara Arslan; Betül Kaya; Alper Kustarci (Cumhuriyet University, 2011)
Purpose: This study investigates the effects of Nd:YAG laser irradiation and 17% EDTA irrigation on apical seals with clearing technique, when used prior to two root canal filling techniques. Material and Methods: Sixty freshly extracted human mandibular premolar and canine teeth, each with one root canal, were instrumented with Protaper rotary nickel-titanium instruments and then randomly divided into six groups according to the final irrigation solutions and Nd:YAG laser irradiation for smear layer removal and obturation techniques employed: Group I: 2.5% sodium hypochlorite (NaOCl) and cold lateral condensation technique, Group II: 17% EDTA and cold lateral condensation technique, Group III: Nd:YAG laser and cold lateral condensation technique, Group IV: 2.5% NaOCl and thermoplasticised injectable gutta-percha technique (Dia-Gun system), Group V: 17% EDTA and Dia-Gun system, Group VI: Nd:YAG laser and Dia-Gun system. After obturation, the root surfaces were coated with a double layer of nail varnish, with the exception of the apical 2 mm, and placed in indian ink for 7 days. All samples were rendered transparent to measure the maximum linear dye penetration. Results: Group 1 showed significantly greater dye leakage compared with groups 5 and 6 (P<0.05). However, no significant difference was found between other groups (P>0.05). Canals obturated with Dia-Gun system showed less mean dye leakage than canals obturated with lateral condensation. Groups, finally irrigated with 17%EDTA and irradiated with Nd:YAG laser, were showed lower mean dye leakage than control groups for both obturation techniques. Conclusion: Under in vitro conditions, we found that smear layer removal improved the ability of the filling materials to prevent the fluid movement. Also, Dia-Gun system showed less apical leakage than cold lateral condensation technique in the presence or absence of the smear layer. Keywords: Apical leakage, Dia-Gun, EDTA, Nd:YAG laser, clearing technique